Assessment of hemoglobin responsiveness to epoetin alfa in patients on hemodialysis using a population pharmacokinetic pharmacodynamic model. (21st July 2015) - Wu, Liviawati; Mould, Diane R.; Perez Ruixo, Juan Jose; Doshi, Sameer
Abstract A population pharmacokinetic pharmacodynamic (PK/PD) model describing the effect of epoetin alfa on hemoglobin (Hb) response in hemodialysis patients was developed. Epoetin alfa pharmacokinetics was described using a linear 2‐compartment model. PK parameter estimates were similar to previously reported values. A maturation‐structured cytokinetic model consisting of 5 compartments linked in a catenary fashion by first‐order cell transfer rates following a zero‐order input process described the Hb time course. The PD model described 2 subpopulations, one whose Hb response reflected epoetin alfa dosing and a second whose response was unrelated to epoetin alfa dosing. Parameter estimates from the PK/PD model were physiologically reasonable and consistent with published reports. Numerical and visual predictive checks using data from 2 studies were performed. The PK and PD of epoetin alfa were well described by the model.